2003
DOI: 10.2308/jmar.2003.15.1.193
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Investigation of the Performance Consequences of Nonfinancial Measures

Abstract: Firms are increasingly implementing new performance measurement systems to track nonfinancial metrics such as customer and employee satisfaction, quality, market share, productivity, and innovation. This study examines the implications of nonfinancial performance measures included in compensation contracts on current and future performance. Contextual factors, environmental factors, and strategic plans vary across firms and, in turn, adopting appropriate nonfinancial measures determines the performance consequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
252
0
11

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(285 citation statements)
references
References 53 publications
22
252
0
11
Order By: Relevance
“…However, not many studies have been conducted that investigate the consequences of SPMS on competitive advantage. Prior studies such as by Henri (2006a), Said et al (2003) examined the effect of SPMS on performance, particularly financial performance. This study operationalise competitive advantage based on the suggestion by Day and Wesley (1988) and Fitzgerald et al (1991).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, not many studies have been conducted that investigate the consequences of SPMS on competitive advantage. Prior studies such as by Henri (2006a), Said et al (2003) examined the effect of SPMS on performance, particularly financial performance. This study operationalise competitive advantage based on the suggestion by Day and Wesley (1988) and Fitzgerald et al (1991).…”
Section: Resultsmentioning
confidence: 99%
“…According to them, these four elements are each necessary but are not individually sufficient for creating 'positional advantage'. Only collectively can they help an organisation be unique and gain an edge over their competitors (Hult & Ketchen, 2001;Henri, 2006a) Many studies had been done to examine the performance effect of performance measurement system for example Davis and Albright (2004) ;Said, HassabElnaby, and Wier (2003);and Ittner and Larcker (2001). However, not much attention has been given to the performance effect from the perspective of RBV.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is a potentially important finding because extant work that models the choice of non-financial measures omits this variable from analysis (e.g., Ittner, Larcker and Rajan 1997;Said, HassabElnaby and Wier 2003). Our theory suggests that non-financial measures are used in response to increasing interdependencies because they are able to reduce the noise in accounting measures.…”
Section: Discussion Limitations and Conclusionmentioning
confidence: 98%
“…Ittner (2008) provides an overview of the statistical evidence on the performance consequences of intangible asset measurement. There are some evidences that non-financial performance measures are positively associated with performance (Abernethy an Lillis, 1995;Ittner and Larcker, 1995;1997;Chenhall, 1997;Perera, Harrison and Pole, 1997;Ittner et al, 2003;Kaynak, 2003;Said et al, 2003;Davis and Albright, 2004). It has been suggested that companies adopting performance measurement system would improve their corporate performance and profitability by identifying the causal relationships between actions and performance (Buhaovac and Slapničar (2007).…”
Section: Balanced Scorecard and Organizational Performancementioning
confidence: 99%